Pendampingan Manajemen Promosi berbasis Digital pada Klinik Masyithoh Muslimat NU Jepara - Subaidi Subaidi; Rony Wijanarko; Nugroho Eko Budiyanto; Murniati Murniati; Azzah Norlaila; Muhammad Dhiyaul Haq; Latifatul Masruroh (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2024)
ABSTRACTMasyithoh Muslimat NU Clinic is one of the health clinics located in the Jepara area, precisely on Jalan Pemuda Number 51 Potroyudan Jepara Village. In carrying out its activities in addition to being supervised by the Jepara Regional Klink Association, it is also by the Nahdlatul Ulama Board of Jepara Regency, Central Java. The quality management of public health services at the clinic needs to be improved, considering that health services are very important and play a role as the foundation of the nation's welfare. Priority issues agreed with partners focus on management and promotion aspects. Target outputs and achievements of this service -Increased quality management of the Masyithoh Muslimat NU Jepara Clinic management reached 100%. Increased partner human resources in managing communication and public service reached 100%. Administrative services are more varied and available online services increased by 90%. Improved online-based partner promotional media increased by 90%. Partner human resources increased their skills in making promotions with attractive graphic designs by 90%. Keywords: Management, Promotion, Digital, Clinic  ABSTRAKMasyithoh Muslimat NU Clinic is one of the health clinics located in the Jepara area, precisely on Jalan Pemuda Number 51 Potroyudan Jepara Village. In carrying out its activities in addition to being supervised by the Jepara Regional Klink Association, it is also by the Nahdlatul Ulama Board of Jepara Regency, Central Java. The quality management of public health services at the clinic needs to be improved, considering that health services are very important and play a role as the foundation of the nation's welfare. Priority issues agreed with partners focus on management and promotion aspects. Target outputs and achievements of this service -Increased quality management of the Masyithoh Muslimat NU Jepara Clinic management reached 100%. Increased partner human resources in managing communication and public service reached 100%. Administrative services are more varied and available online services increased by 90%. Improved online-based partner promotional media increased by 90%. Partner human resources increased their skills in making promotions with attractive graphic designs by 90%. Kata Kunci: Digital, Klinik, Manajemen, Promosi